Differential degradation of intact polar and core glycerol dialkyl glycerol tetraether lipids upon post-depositional oxidation - Lengger, Sabine; Kraaij, M.; Tjallingii, R.; Baas, M.; Stuut, J.; Hopmans, E.; Damste, J.; Schouten, S. (Pergamon, 2013)
Archaeal and bacterial glycerol dialkyl glycerol tetraether lipids (GDGTs) are used in various proxies, such as TEX86 and the BIT index. In living organism, they contain polar head groups (intact polar lipids – IPLs). IPL GDGTs have also been detected in ancient marine sediments and it is unclear whether or not they are fossil entities or are part of living cells. In order to determine the extent of degradation of IPL GDGTs over geological timescales, we analyzed turbidite deposits, which had been partly reoxidized for several kyr after deposition on the Madeira Abyssal Plain. Analysis of core lipid (CL) and IPL-derived GDGTs showed a reduction in concentration by two orders of magnitude upon post-depositional oxidation, while IPL GDGTs with a mono- or dihexose head group decreased by 2–3 orders of magnitude. The BIT index for CL- and IPL-derived GDGTs increased substantially upon oxidation from 0.1 to up to 0.5. Together with changing MBT/CBT values, this indicates preferential preservation of soil-derived branched GDGTs over marine isoprenoid GDGTs, combined with in situ production of branched GDGTs in the sediment. The TEX86 value for IPL-derived GDGTs decreased by 0.07 upon oxidation, while that of CL GDGTs showed no significant change. Isolation of IPLs revealed that the TEX86 value for monohexose GDGTs was 0.55, while the that for dihexose GDGTs was substantially higher, 0.70. Thus, the decrease in TEX86 for IPLderived GDGTs was in agreement with the dominance of monohexose GDGTs in the oxidized turbidite, probably caused by a combination of in situ production as well as selective preservation of terrestrial isoprenoid GDGTs. Due to the low amount of IPL GDGTs vs. CL GDGTs, the impact of IPL degradation on CLbasedTEX86 paleotemperature estimates was negligible.